Thursday

April 17, 2014

April 17, 2014

Posted by **shay** on Wednesday, April 16, 2008 at 9:39am.

solve p-1/2-p-2/3=1

(3p-3)-(2p-4)/6=1

- maths -
**Jake1214**, Wednesday, April 16, 2008 at 12:20pmThe way you put it, there's no multiplication... so I don't know where you get 3p and 2p... maybe you want to revise your original problem by addiing in the parentheses.

Anyway, by the way you put it... it should be:

p-p-1/2-2/3=1 (combine like-terms)

0-3/6-4/6=1 (common denominator)

-7/6=1 (subtraction)

... and you end up with a false statement, yep, you need to revise your problem so people can read it correctly.

**Related Questions**

Math - Which is the expression that can be factored using the greatest common ...

Chemistry - In which orbital does an electron in a phosphorus atom experience ...

math grade nine - can someone please tell me if this answer is correct p-3+2p-9=...

Chemistry - Which of the following electron configurations is not consistent ...

Chemistry - Which of the following electron configurations is not consistent ...

maths - If x is a Poisson variate such that 3p (x=2) = 2p (x=1). Find 1. p (x=0...

maths - If x is a Poisson variate such that 3p (x=2) = 2p (x=1). Find 1. p (x=0...

maths - If x is a Poisson variate such that 3p (x=2) = 2p (x=1). Find 1. p (x=0...

Math - Solve. 3p-1=5(p-1)-2(7-2p)

Algebra 1- 8th Grade - How do you solve these types of problems? 1) 3 - n = 32 ...